The Implementation Of Health Information with Clean And Healthy Living Behavior in Fifth Grade Students At Elementry School Lhoksukon Aceh Utara - Rosmalina; Liza Phonna (Akademi Keperawatan Kesdam Iskandar Muda Lhokseumawe, 2022)
The implementation of healthy and clean behaviour in Indonesia is relatively low. According to the Ministry of Health of the Republic of Indonesia in 2016, the decline in health and clean living practices in Nanggroe Aceh Darusslam was as much as 28.6% in 2016 more than to previous years. The purpose of this study was to determine the implementation of health education, namely clean and healthy living behavior in fifth grade students at SDN 3 Lhoksukon North Aceh in 2021. This type of research is qualitative. The data was collected and analyzed based on the theory found to draw a conclusion. This appropriate to the purpose of the research. Finally, this research can be concluded that most of the students received health education in the good category. This good health education was obtained by students from health workers from the UKS program at the Lhoksukon Health Center. In addition, students also receive health education from teachers, especially physical education teachers.